Hinokitiol is a novel glycoprotein VI antagonist on human platelets. (December 2014) - Lu, Wan-Jung; Wu, Ming-Ping; Lin, Kuan-Hung; Lin, Yu-Chen; Chou, Hsiu-Chu; Sheu, Joen-Rong
Abstract Hinokitiol (4-isopropyl-tropolone) is a bioactive compound with various pharmacological activities that is found in the wood of cupressaceous plants. Platelet activation plays an important role in thrombogenesis. In our previous study, hinokitiol specifically inhibited collagen-induced platelet aggregation ex vivo and prolonged thrombogenesis in vivo. The glycoprotein (GP) VI and integrin α2β1 are major collagen receptors that mediate platelet adhesion and aggregation. In our current study, we investigated which of these collagen receptors is involved in the hinokitiol-mediated inhibition of platelet activation. Treatment with 2–100 µM hinokitiol caused a dose-dependent right, parallel shift in the collagen concentration–response curve (0.5–10 µg/ml), with no change in the maximal responses. Furthermore, hinokitiol inhibited platelet aggregation and relative [Ca2+]i mobilization stimulated by convulxin, an agonist of GP VI, but not by aggretin, an agonist of integrin α2β1, indicating that hinokitiol mediates the inhibition of platelet activation through GP VI, rather than through integrin α2β1. Hinokitiol also specifically inhibited the convulxin-mediated activation of protein kinase C, phospholipase Cγ2, Akt, mitogen-activated protein kinases, and Lyn. Hinokitiol markedly diminished the co-immunoprecipitation of GP VI-bound Lyn after convulxin stimulation. In conclusion, hinokitiol, an antagonist of collagen GP VI may represent a novel antiplatelet drug for the prevention of thrombi associated with coronary and cerebral artery diseases.